STRIVING FOR SUPERIORITY OF KING LEONIDAS IN ZACK SNYDER'S 300 MOVIE : AN INDIVIDUAL PSYCHOLOGICAL APPROACH - Afada, Rahmat Rozin (2011)
The problem of this study is to reveal how striving for superiority on the major character. The objectives of the study are to analyze the movie based on the major character in Zack Snyder's 300 movie based on Individual Psychological Analysis. The study is a literary study, which can be categorized into a qualitative study. The object of this study is Zack Snyder 300 movie. The data sources are primary and secondary data sources. The primary data sources the movie 300 script and the secondary data are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer draws some conclusions as follows: first, Zack Snyder's 300 movie tells about the major character as king Leonidas is strive for his superiority to go out of his condition. Second, every people has many ways to striving for superiority. In 300 movie, the major character, king Leonidas does some efforts to strive his superiority that represents a case study of individual psychology.